2022
DOI: 10.1002/hpja.574
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol spectrum disorder resources for educators: A scoping review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Finally, teachers in the current study emphasized a need for evidence‐based information and strategies and difficulty knowing whether information they came across was accurate. This reflects results of a recent scoping review which suggested few FASD resources for educators are formally evaluated (Lees et al, 2022). Some research has suggested intervention feasibility and appropriateness are more important to teachers compared to an evidence base (Boardman et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Finally, teachers in the current study emphasized a need for evidence‐based information and strategies and difficulty knowing whether information they came across was accurate. This reflects results of a recent scoping review which suggested few FASD resources for educators are formally evaluated (Lees et al, 2022). Some research has suggested intervention feasibility and appropriateness are more important to teachers compared to an evidence base (Boardman et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…Given the need for evidence‐based, FASD‐informed resources for teachers (Lees et al, 2022), the Families Moving Forward (FMF) program was identified as an FASD intervention that could be efficiently and successfully adapted to teachers. The FMF Program is an evidence‐based behavioral consultation program for caregivers of children with FASD, developed at Seattle Children's Research Institute/University of Washington by Heather Carmichael Olson and colleagues (Bertrand, 2009; Olson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still very few interventions specifically for individuals with prenatal alcohol exposure, though there have been more resources that have been made available to schools [60 ▪ ], justice systems, parents and healthcare settings to help improve outcomes. There is also great opportunity for the repurposing of interventions that can target specific behaviors associated with prenatal alcohol exposure, if they are implemented effectively (e.g.…”
Section: Intervention Modalities and Targetsmentioning
confidence: 99%
“…The literature surrounding this disorder calls for an accurate and universal detection and diagnostic system that enables early identification of its core manifestations [ 2 , 3 ]. Based on these arguments and considering the prevalence data in Spain, estimated at 22.2% cases of FASD per 10,000 inhabitants [ 4 ], as well as the lack of knowledge among healthcare and educational professionals regarding this disorder [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], it is essential to have a behavioral and cognitive profile that considers the developmental stage.…”
Section: Introductionmentioning
confidence: 99%